NAFTA AT 21: STRUCTURAL CHANGE IN MEXICAN’S DEMAND FOR U.S. MEAT AND MEAT PRODUCTS - Frank Kyekyeku Nti (International Journal of Food and Agricultural Economics, 2016)
The purpose of this paper is to examine the influence of the North American Free Trade Agreement (NAFTA) on the change in consumer preference for U.S. meat and meat products in Mexico and to provide empirical estimates of the extent of sensitivity of meat price change to change in quantity demand. The analyses used an Inverse Almost Ideal Demand System (IAIDS) model to address the study objectives due to its appropriateness in modeling the level of utility for commodities with fixed or exogenously determined short run supply. The study findings show that Mexico’s participation in NAFTA could have indirectly effected a structural change in demand for imported meat from the U.S. but the direction of change is heterogeneous among the different meat groups. Also, while Mexican demand for U.S. meat is inflexible, price response to changes in the quantity of imported U.S. poultry is much sensitive compared to pork and beef.